1999
DOI: 10.1021/ja990513+
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Fluorophore Functionalization of Water-Soluble, Tiopronin-Protected Gold Clusters

Abstract: Place-exchange and amide-forming coupling reactions represent two facile and efficient routes to poly-functionalization of water-soluble nanoparticles. In this paper, place-exchange and amide-forming coupling reactions with water-soluble tiopronin-MPCs are described and their products characterized by 1H and 31P NMR, capillary electrophoresis, electrochemistry, and fluorescence spectroscopy. Place-exchange reactions of ligands with tiopronin-MPCs yield products with about half of the ligand exchange expected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
277
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(285 citation statements)
references
References 36 publications
6
277
1
1
Order By: Relevance
“…In 1998, Wilcoxon et al reported blue emission at 440 nm from small gold nanoparticles (diameter < 2.5 nm) (67), however, due to the heterogeneity of the solution, the exact size of emissive species was undetermined. Near IR emission was also reported from glutathione encapsulated Au 28 clusters (9) and from tiopronin-capped ~1-nm Au species (68)(69)(70)(71)(72)(73)(74)(75), both in aqueous solution. Compared to well-studied alkali clusters (24,25), the size-dependent electronic structure of these noble metals remained poorly understood, yet a framework (9,23,76) for linking nanoparticle and cluster optical properties through free electron scalings was in place.…”
Section: Fluorescent Gold Nanoclustersmentioning
confidence: 89%
“…In 1998, Wilcoxon et al reported blue emission at 440 nm from small gold nanoparticles (diameter < 2.5 nm) (67), however, due to the heterogeneity of the solution, the exact size of emissive species was undetermined. Near IR emission was also reported from glutathione encapsulated Au 28 clusters (9) and from tiopronin-capped ~1-nm Au species (68)(69)(70)(71)(72)(73)(74)(75), both in aqueous solution. Compared to well-studied alkali clusters (24,25), the size-dependent electronic structure of these noble metals remained poorly understood, yet a framework (9,23,76) for linking nanoparticle and cluster optical properties through free electron scalings was in place.…”
Section: Fluorescent Gold Nanoclustersmentioning
confidence: 89%
“…The few known precedents of poly-electron transfer reactions include soluble redox polymers 29 and redox-labeled dendrimers. 9 MPCs have been poly-functionalized with ferrocene (e25 sites per MPC), 22a,30 anthraquinone (e25), 31 phenothiazine (e7), 23 and viologen (e36) 26 groupings. Figure 4a illustrates voltammetry 30a of a Fc 9 -MPC solution; analogous ferrocenes have been examined as Langmuir monolayers at the air/water interface.…”
Section: Chemical Properties Of Functionalized Mpcsmentioning
confidence: 99%
“…This report focused on the viability of these water soluble nanoparticles as precursors for both ligand exchange and postsynthetic modification via amide coupling reactions. 40 In the same year, Chen and Kimura reported the synthesis of nanoparticles ranging in size from 1.0 to 3.4 nm by NaBH 4 reduction of HAuCl 4 in the presence of mercaptosuccinic acid, using methanol as a solvent. Although size evolution of the nanoparticle products in solution became apparent over time, the dried nanoparticle powders were stable and completely redispersible in water.…”
Section: Thiol-stabilized Nanoparticlesmentioning
confidence: 99%
“…Candidates for postsynthetic modifications are generally produced by direct synthesis (ω-functionalized particles created by Brust preparations) or sometimes ligand exchange methods (usually involving the introduction of a ligand bearing a reactive pendant functional group). Modification reactions include polymerizations, [213][214][215][216] coupling reactions, 40,48,[217][218][219][220][221] or transformation of an existing chemical moiety. 48,[222][223][224] In all cases, the success of such modifications relies not only on the nanoparticles' tolerance for various reaction conditions but also on the overall reactivity and steric environment presented by functional groups that are constrained through binding to a nanoparticle.…”
Section: Postsynthetic Modification Of the Ligand Shellmentioning
confidence: 99%